10 Little Monsters Visit Texas - Madson, Trish; Sims, Sean ([Sanger, CA] : Familius LLC, 2017)
From the Denver Zoo to the Royal Gorge Bridge and Pikes Peak, these 10 Little Monsters discover some of the most unique and interesting things about Colorado and what it has to offer. Silly, over-the-top fun, and a bit macabre, 10 Little Monsters Visit Colorado is the perfect book for every little boy and ghoul!
Keywords: Monsters -- Juvenile fiction; Counting -- Juvenile fiction; Colorado -- Juvenile fiction; Stories in rhyme